2017
DOI: 10.1002/cbin.10783
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression changes of thermo‐sensitive transient receptor potential channels in obese mice

Abstract: Adipose tissues play key roles in energy homeostasis. Brown adipocytes and beige adipocytes in white adipose tissue (WAT) share the similar characters of thermogenesis, both of them could be potential targets for obesity management. Several thermo-sensitive transient receptor potential channels (thermoTRPs) are shown to be involved in adipocyte biology. However, the expression pattern of thermoTRPs in adipose tissues from obese mice is still unknown. The mRNA expression of thermoTRPs in subcutaneous WAT (sWAT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 37 publications
2
30
0
Order By: Relevance
“…TRPV3 could be primarily activated by a high noxious threshold which is over 50°C and then becomes responsive to warm temperatures [66]. It has been reported that the expression level of TRPV3 was decreased in visceral adipose tissue in HFD-treatment mice, ob/ob and db/db mice [67], and also reduced in subcutaneous WAT and interscapular BAT in HFD-treated and db/db mice, which is similar to TRPV1 [68]. HFD feeding increases TRPV3 expression in the medial nucleus tractus solitarius (mNTS) and hypoglossal nucleus (HN) in rats, which is accompanied by a reduced expression of proopiomelanocortin (POMC) and resulted in increased food intake and a gain of body-weight [69].…”
Section: Trpv Family In Adipogenesismentioning
confidence: 85%
See 1 more Smart Citation
“…TRPV3 could be primarily activated by a high noxious threshold which is over 50°C and then becomes responsive to warm temperatures [66]. It has been reported that the expression level of TRPV3 was decreased in visceral adipose tissue in HFD-treatment mice, ob/ob and db/db mice [67], and also reduced in subcutaneous WAT and interscapular BAT in HFD-treated and db/db mice, which is similar to TRPV1 [68]. HFD feeding increases TRPV3 expression in the medial nucleus tractus solitarius (mNTS) and hypoglossal nucleus (HN) in rats, which is accompanied by a reduced expression of proopiomelanocortin (POMC) and resulted in increased food intake and a gain of body-weight [69].…”
Section: Trpv Family In Adipogenesismentioning
confidence: 85%
“…TRPV2 and TRPV4 function as an osmo-and/or mechano-sensor, which could be activated by hypotonic solution or mechanical stimulation [70][71][72][73]. TRPV2 has also been reported to be expressed in both WAT and BAT [68,74], which can be activated by noxious heat with the threshold above 52°C [75]. The expression level of TRPV2 is higher in mature adipocytes than in pre-adipocytes.…”
Section: Trpv Family In Adipogenesismentioning
confidence: 99%
“…and Trpv3 mRNA were significantly decreased, whereas Trpv2 and Trpv4 mRNA were significantly increased in WAT of either db/db or diet-induced obesity mice [42]. It has been reported that TRPV1…”
Section: Discussionmentioning
confidence: 93%
“…Recent research has also characterized the expression of TRPV1 in these tissues. TRPV1 expression has been shown on cultured adipocytes [90][91][92] and epididymal, subcutaneous and brown adipocytes [6,7,93]. The validation of expression of TRPV1 on adipose tissues suggests a plausible role of TRPV1 in the recruitment of BAT activity and thermogenesis and the induction of the molecular conversion of WAT to beige like cells.…”
Section: Adipose Depots Functions and Trpv1 Expressionmentioning
confidence: 87%